HOWCAN MULTI- CHANNEL RETAILING FURTHER EXPAND THEIR PRODUCT RANGE WHILST SUSTAINING CUSTOMER EXPERIENCE AND SATISFACTION FOR BOOTS.COM? A Risk management perspective - Mohd Ramli, Mohd Nizaruddin Azlan (2008)
Albert Einstein (1923) once said 'You believe in a God who plays dice, and I am in complete law and order in a world which objectively exists. God does not play with dice in nature, the outcomes of most of the risks we create; depend on the decisions of other human being especially in business'. This landmark speech charts the extraordinary advances that mankind has made to control destiny. Thus, in risk management, controlling risk goes beyond understanding it, measuring it, and weighing its consequences, but taking it on a journey. Boots.com has delivered many customer led initiatives designed to build a base for the future, including extending range (e.g. Beauty Beautique), adding Expertise & Advice (e.g. BMJ), improving website experience (e.g. new look & feel), building our infrastructure (100% warehouse, new IT architecture, out-sourcing fraud), building a strong team, supported by industry experts (increased +10 FTE's). As one of the 20 transformation initiatives for Boots.com, it launched a new web platform on 27th August 2008, which will enable them to move towards a multi channel business model. This platform provides a base from which to build a multi-channel business model. Boots.com believes that the markets in which we operate will fundamentally change over thenext 10 years. Thus, Boots.com must create a multi-channel business model in order to thrive and meet the key challenges we face, as well as exploit opportunities This paper is the Individual Project by taking a Risk Management perspective from the Main Theme: How can multi-channel retailing further expand their product range whilst sustaining customer experience and satisfaction for Boots.com? In the course of the writing, the author has dealt heavily with the literature reviews surrounding Risk Management, Risk Assessment, Risk Analysis, Risk Identification, Risk Mitigation and also its practical applications. The author further focuses on exploiting oppurtunities for Boots.com by considering, insight and interest into risk management aspects of online product range extension, risk management challenges and outcomes for moving into the new market and sustaining competitive advantage, enterprise Risk Management at Boots.com, Inventory, Supply Chain Risk Management for Online Product Range Extension, Financial, legal, and emerging issues in risk, Probabilities, NPVR, Value At Risk and Impact on the Financial Statement; and Real Options and Balance Scorecard. Finally, the author draws conclusion therein and provides recommendation for Boots.com